Pulpal Thermal Changes following Er-YAG Laser Debonding of Ceramic Brackets - Didem Nalbantgil; Murat Tozlu; Mehmet Oguz Oztoprak (The Scientific World Journal)
Lasers are effective in debonding ceramic brackets. Unfortunately, while reducing the adhesive bond strength, lasers are also reported to increase pulpal temperature. The aim of this study was to evaluate the shear bond strengths and temperature increase levels after debonding ceramic brackets using an Er-YAG laser with or without water-cooling. Sixty polycrystalline upper premolar ceramic brackets were placed on the labial surface of sixty human premolar teeth which were randomly divided into three groups of twenty. A laser pulse at 5 W for 9 seconds was delivered to each bracket in both study groups either with water-cooling (water group) or without water-cooling (waterless group) using an Er-YAG laser. Debonding was performed 45 seconds after laser exposure and shear bond strengths were measured. Data comparison revealed a statistically significant difference between the groups. Mean temperature increases of 2.41°C and 4.59°C were recorded for the water and waterless laser groups, respectively. The shear bond strength value for the control group was 22.76 MPa and 10.46 and 6.36 MPa for the water and waterless laser groups, respectively. The application of Er-YAG laser with water-cooling was an efficient and safe method of debonding ceramic brackets.